2017
DOI: 10.1177/2398212817721859
|View full text |Cite
|
Sign up to set email alerts
|

Retrosplenial and postsubicular head direction cells compared during visual landmark discrimination

Abstract: Background:Visual landmarks are used by head direction (HD) cells to establish and help update the animal’s representation of head direction, for use in orientation and navigation. Two cortical regions that are connected to primary visual areas, postsubiculum (PoS) and retrosplenial cortex (RSC), possess HD cells: we investigated whether they differ in how they process visual landmarks.Methods:We compared PoS and RSC HD cell activity from tetrode-implanted rats exploring an arena in which correct HD orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…The existence of egocentric boundary cells (EBC) was proposed by Derdikman (2009), and EBC were recently identified in the entorhinal cortex (Wang et al 2018, Gofman et al 2019), postrhinal cortex (Gofman et al 2019), parasubiculum (Gofman et al 2019), striatum (Hinman et al 2019) and RSC (Alexander et al 2019). Several studies have described HDC in the RSC (Chen et al 1994a,b; Cho et al 2001; Jacob et al 2017; Lozano et al 2017). Here we found that, although 28% of RSC cells were tuned to HD, the majority of these were in fact EBC with weaker but significant responses to HD, such that only 4% of RSC cells were classified as HDC.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of egocentric boundary cells (EBC) was proposed by Derdikman (2009), and EBC were recently identified in the entorhinal cortex (Wang et al 2018, Gofman et al 2019), postrhinal cortex (Gofman et al 2019), parasubiculum (Gofman et al 2019), striatum (Hinman et al 2019) and RSC (Alexander et al 2019). Several studies have described HDC in the RSC (Chen et al 1994a,b; Cho et al 2001; Jacob et al 2017; Lozano et al 2017). Here we found that, although 28% of RSC cells were tuned to HD, the majority of these were in fact EBC with weaker but significant responses to HD, such that only 4% of RSC cells were classified as HDC.…”
Section: Discussionmentioning
confidence: 99%
“…HD cell firing rates can vary between different HD cells (Taube, 2007) and on average the peak firing rate can differ between recording locations within cortical-limbic regions, approximately ranging from 2 spikes/s to 120 spikes/s (Blair and Sharp, 1995;Taube and Muller, 1998;Peyrache et al, 2015;Lozano et al, 2017). Notably, ATN HD cells on average express higher firing rates compared to those recorded in PoS (Blair and Sharp, 1995;Taube and Muller, 1998;Peyrache et al, 2015) and some preliminary work indicates that the firing rates of PaS and MEC HD cells are on average lower than ATN cells (Winter et al, 2015b).…”
Section: Firing Ratementioning
confidence: 99%
“…For instance, Clark et al (2010) showed that large lesions of the RSC can impair control over anterior thalamic head direction cell activity typically exerted by a prominent environmental landmark. Briefly, when a landmark is manipulated in an environment, limbic head direction cells maintain their orientation in relation to the cue Lozano et al, 2017;Yoder et al, 2011b). However, in animals with RSC lesions, anterior thalamic head direction cells were no longer controlled by the cue, and would adopt other orientations, perhaps in reference to other stimulus sources (Clark et al, 2010).…”
Section: Reference Frame Coding By Retrosplenial Cortical Neuronsmentioning
confidence: 99%